Effect of folic acid by mouth on cerebrospinal fluid homovanillic acid and 5-hydroxyindoleacetic acid concentration - Hunter, Richard (1971)
Administration of 30 mg folic acid by mouth caused a significant fall in cerebrospinal fluid homovanillic acid concentration in 11 subjects. There was no significant change of 5-hydroxyindoleacetic acid concentration. The fall was less marked in five patients on anticonvulsant medication and failed to reach statistical significance. Neither homovanillic acid nor 5-hydroxyindoleacetic acid concentrations changed significantly when 15 mg folic acid was given in divided dosage for one, two, and four weeks. The effect appeared to be related to the height of serum-folate levels reached and to be independent of cerebrospinal fluid-folate levels, which did not change significantly. Possible mechanisms and their potential therapeutic application are discussed.